Comprehensive analysis of a novel cuproptosis-related lncRNA signature associated with prognosis and tumor matrix features to predict immunotherapy in soft tissue carcinoma - Liu, Binfeng; Pang, Ke; Feng, Chengyao; Liu, Zhongyue; Li, Chenbei; Zhang, Haixia; Liu, Ping; Li, Zhihong; He, Shasha; Tu, Chao (Frontiers in Genetics, 2022)
Background: A crucial part of the malignant processes of soft tissue sarcoma is played by cuproptosis and lncRNAs (STS). However, the connection between cuproptosis-related lncRNAs (CRLs) and STS is nevertheless unclear. As a result, our objective was to look into the immunological activity, clinical significance, and predictive accuracy of CRLs in STS. Methods: The TCGA and GTEx databases, respectively, provided information on the expression patterns of STS patients and the general population. Cuproptosis-Related lncRNA Signature (CRLncSig) construction involved the multivariate Cox regression analysis together with the univariate least absolute shrinkage and selection operator. The predictive performance of the CRLncSig was evaluated using a serial analysis. Further research was done on the connections between the CRLncSig and the tumor immune milieu, somatic mutation, immunotherapy response, and chemotherapeutic drug susceptibility. Notably, an in vitro investigation served to finally validate the expression of the hallmark CRLs. Results: low-CRLncSighigh-CRLncSiglow-CRLncSigA novel efficient CRLncSig composed of seven CRLs was successfully constructed. Additionally, the low-CRLncSig group's prognosis was better than that of the high-CRLncSig group's based on the new CRLncSig. The innovative CRLncSig then demonstrated outstanding, consistent, and independent prognostic and predictive usefulness for patients with STS, according to the evaluation and validation data. The low-CRLncSig group’s patients also displayed improved immunoreactivity phenotype, increased immune infiltration abundance and checkpoint expression, and superior immunotherapy response, whereas those in the high-CRLncSig group with worse immune status, increased tumor stemness, and higher collagen levels in the extracellular matrix. Additionally, there is a noticeable disparity in the sensitivity of widely used anti-cancer drugs amongst various populations. What’s more, the nomogram constructed based on CRLncSig and clinical characteristics of patients also showed good predictive ability. Importantly, RT-qPCR demonstrated that the signature CRLs exhibited a significantly differential expression level in STS cell lines. Conclusion: In summary, this study revealed the novel CRLncSig could be used as a promising predictor for prognosis prediction, immune activity, tumor immune microenvironment, immune response, and chemotherapeutic drug susceptibility in patients with STS. This may provide an important direction for the clinical decision-making and personalized therapy of STS.